The problem of media coverage of contemporary Arab formation - Asaad Abdul Mohsen Ali Hussain; Bahaa Abdel Hussein Majeed (Basrah Arts Journal, 2023)
Deciphering the codes of contemporary plastic art requires an intellectual effort, so that communication between the artist and the media outlet can strip away the ambiguity to reach a clear reading such that the achievement can be understandably presented to the recipient. The first chapter serves to identify the problem, the scope of the study. As the issue stems from the ambiguous nature of an artist’s piece for media publication, it would derive several questions: What is the level of interest of the Arab press in the field of plastic arts? How willing is the Arab press to actively contribute to the field? And are they open to enhancing the process of understanding or receiving it? The author(s) further elaborate upon the importance and aim of the research that is quantified by the objective and temporal metrics of the study along with relevant, defined terminology. The second chapter covers the two concepts of information and receiving through its design of the study’s theoretical framework and the author(s) acknowledgment and citations of prior relevant works. Its third chapter details the procedures by which the researcher(s) would identify a sample populace consisting of chosen relatives and relevant works of art. The fourth chapter, in providing its analysis of the results and the drawn conclusions of the study, gave insight into how media and art can influence an audience’s opinions about community issues. Such a connection would notably contribute to the decision-making process and shape the convictions of the individual..